2010
DOI: 10.1021/nl1007079
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Electrospun Nanofiber Composite Membranes for Fuel Cell Electrolytes

Abstract: We have synthesized the novel composite membranes composed of sulfonated polyimide nanofibers and sulfonated polyimide for proton exchange membrane fuel cell. It was clear that the polyimides within nanofiber were significantly oriented or aggregated when electrospun; as the result, the membrane stability, such as oxidative and hydrolytic stabilities, of the composite membrane was significantly improved with an increase in nanofiber, and oxygen permeability of the composite membrane also decreased when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
167
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(174 citation statements)
references
References 29 publications
7
167
0
Order By: Relevance
“…Interestingly, it has been found that proton conducting nanofibers exponentially increase conductivity with decrease in fiber diameter [25,31]. Higher increment of the proton conductivity is observed along the fiber axis direction than perpendicularly, which is attributed to the preferential orientation of the sulfonated polymeric chains and the consequent alignment of the ionic channels [21,22]. On the other hand, it has been suggested that proton transport takes place preferentially on the surface of the nanofibers, enriched with ionic clusters, rather than inside the nanofiber structure [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been found that proton conducting nanofibers exponentially increase conductivity with decrease in fiber diameter [25,31]. Higher increment of the proton conductivity is observed along the fiber axis direction than perpendicularly, which is attributed to the preferential orientation of the sulfonated polymeric chains and the consequent alignment of the ionic channels [21,22]. On the other hand, it has been suggested that proton transport takes place preferentially on the surface of the nanofibers, enriched with ionic clusters, rather than inside the nanofiber structure [32].…”
Section: Introductionmentioning
confidence: 99%
“…This approach involves electrospinning a polymer solution to obtain a nanofiber mat which is afterwards filled with a proton conductive polymer matrix [21][22][23][24][25][26][27][28], although insulating polymers infiltrated into proton conductive nanofibers has also been proposed [29,30]. Interestingly, it has been found that proton conducting nanofibers exponentially increase conductivity with decrease in fiber diameter [25,31].…”
Section: Introductionmentioning
confidence: 99%
“…Specific applications include tissue scaffolds [3][4][5][6][7][8][9][10][11], membranes for fuel cells [12], separation layers for batteries [13], air and water filtration [14,15], reinforcement for nano-composites [2,[16][17][18], piezoelectric fibres for energy harvesting and sensors [19][20][21] and conductive layers in solar cells and electronics [17,21,22]. Electrospinning compares favourably with other methods of nano-fibre manufacture such as drawing, template synthesis, phase separation and self-assembly due to its relative simplicity and low cost [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…8 We have reported novel uniaxially and biaxially aligned fluorinated polyimide nanofibers using specially designed collectors. 15,16 Most recently, we first attempted the preparation of electrospun polyimide nanofibers for electrical conductive materials by a carbonization method using ion-beam irradiation. 17 Ion-beam irradiation is a well-established technique for the postprocessing of materials and has been recognized as an effective method for the synthesis, modification and fabrication of materials, including polymers.…”
Section: Introductionmentioning
confidence: 99%
“…We chose polyimides and PSF for several reasons: they easily provide nanofibers by the electrospinning method [13][14][15][16] and have distinctive thermal and mechanical properties that may help to maintain the nanofiber structures after ion-beam irradiation. 17 PAN was chosen because there have been many reports on carbon fibers prepared from PAN fibers by thermal carbonization.…”
Section: Introductionmentioning
confidence: 99%